Diagnostic Performance of Focused Cardiac Ultrasound Performed by Emergency Physicians for the Assessment of Ascending Aorta Dilation and Aneurysm. (21st April 2015) - Nazerian, Peiman; Vanni, Simone; Morello, Fulvio; Castelli, Matteo; Ottaviani, Maddalena; Casula, Claudia; Petrioli, Alessandra; Bartolucci, Maurizio; Grifoni, Stefano; Moore, Christopher
Abstract Objectives The diagnostic performance of transthoracic focused cardiac ultrasound (FoCUS) performed by emergency physicians (EP) to estimate ascending aorta dimensions in the acute setting has not been prospectively studied. The diagnostic accuracy and the interobserver variability of EP‐performed FoCUS were investigated to estimate thoracic aortic dilation and aneurysm compared with the results of computed tomography angiography (CTA). Methods This was a prospective single‐center cohort study of a convenience sample of patients who underwent CTA in the emergency department for suspected aortic pathology. FoCUS was performed before CTA, and the maximum ascending aorta diameter evaluated in parasternal long‐axis view. Aorta diameter < 40 mm by visual estimation or by diameter measurement was considered normal. Measurements were recorded in all patients with aorta diameter ≥ 40 mm. Diagnostic accuracy of FoCUS for detection of aortic dilation (diameter ≥ 40 mm) and aneurysm (diameter ≥ 45 mm) were calculated considering the CTA result as reference standard. In a subgroup of patients, a second EP‐sonographer performed FoCUS to evaluate interobserver agreement for the diagnosis of ascending aorta dilation. Results A total of 140 patients were enrolled in the study. Ascending aorta dilation and aneurysm were detected with FoCUS in 50 (35.7%) and in 27 (17.8%) patients, respectively. Sensitivity and specificity of FoCUS were 78.6% (95% confidence interval [CI] = 65.6% to 88.4%) and 92.9% (95% CI = 85.1% to 97.3%), respectively, for ascending aorta dilation and 64.7% (95% CI = 46.5% to 80.2%) and 95.3% (95% CI = 89.3% to 98.4%), respectively, for ascending aorta aneurysm. Interobserver agreement of FoCUS was k = 0.82. Conclusions FoCUS performed by EP is specific for ascending aorta dilation and aneurysm when compared to CTA and appears a reproducible technique.